Development of a smart elevator using embedded system - Tan, Dicky (2022)

(untitled)
Nowadays, an elevator is a transportation that vertically transports humans or objects between floors of a building, commonly found in multi-storey buildings. However, due to technological advancement and the COVID-19 pandemic, contactless smart elevators are being developed by plenty of companies. In this project, the Arduino Mega 2560 Rev3 and Cytron Wi-Fi Shield is used for the hardware while the MIT App Inventor is used for developing the mobile application. The Arduino Mega Rev3 is used to control the features of the elevator, while the Cytron W-Fi Shield is used to enable the smartphone to connect to the Arduino board via an internet connection, and finally the mobile application developed by using MIT App Inventor will act as the “buttons” of the elevator, to call the elevator and select the destination floor. Additionally, some safety features are implemented in this elevator system, such as the RFID readers and the door sensors. For the RFID readers, it is an alternative method of accessing the elevator and being able to go to the destination floor without using the mobile application while improving the security and the convenience of accessing the elevator by using RFID cards. Meanwhile, a magnetic sensor is used to act as the floor sensor. For the mobile application, the elevator car is able to move to the respective floor based on the buttons pressed from the mobile application. After that, the reliability of the elevator system is analysed, which shows the accuracy of the RFID readers to detect the RFID cards are 100 % for all floor RFID readers and 85 % for admin RFID reader while the accuracy of the magnetic sensors to detect the elevator car when the elevator passes through the sensors are 100%. The overall reliability of the elevator system is tested within 30 minutes, which works reliably and functions well.